Peningkatan Nilai Tambah Mineral Kalsit Menjadi Barang Seni Lampu Hias - Rully Nurhasan Ramadani; M. Imam Aga Dinata; Eka Adhitya; Himawan Nuryahya; Sri Widayati (Jurusan Teknik Pertambangan, Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2021)
Abstract Increasing the added value of rock and minerals can provide benefits to the wider society. The policy conservation of minerals, which has a focus on optimizing benefits and minimizing negative impacts of mining activities. Framework of optimizing the benefits of minerals, there are efforts, maintenance, protection, mining and processing as well as increasing the added value og these minerals. Calcite mineral (CaCO3) a part of the carbonate mineral group as one of the main composition mineral of limestone. The utilization of this calcite mineral is reviewed based on the quality of the physical and chemical properties. In principle, this research utilize the physical properties of the mineral because the chemical quality is relative low. Trial and error method is used in this study to getting the right design of art. The processing is simple and doest not require high technology and certified skills, by utilizing the transparency, color, and gloss properties of the mineral calcite will become an art item that has added value when given lighting. Keywords: Calcite, Added Value, Art Items, Decorative Lighting